Protective equipment-related pressure ulcers in healthcare workers during COVID-19 pandemic: A systematic review - (:unkn) unknown (My University, 2022)
Aim: This systematic review was carried out to examine pressure ulcers in healthcare staff due to the use of protective equipment during COVID-19 pandemic and the precautions taken to prevent these injuries. Method: Relevant studies were retrospectively searched. Seven English keywords identified from MESH were used while searching. The search was carried out in five international databases by trying various combinations of these words during February 15–25, 2021. This systematic review was updated by rescanning databases on December 20, 2021 and a total of 611 studies were attained. Results: 17 studies which met the study inclusion criteria, which were conducted mostly through online survey method in different study designs and which included a total of 24,889 healthcare professionals were examined. The incidence of PPE-related pressure ulcers was found to be between 30% and 92.8%. Grade I pressure ulcers were the most common (44.1%–82%). The incidence of skin problems except PPE-related pressure ulcers such as itching, redness and dry skin was found to be between 42.8–88.1%. Risk factors that frequently played a role in the development of PPE-related pressure ulcers and other skin problems were longer use of PPE and sweating. PPE-related pressure ulcers and other skin problems were more frequent over the nose (nasal bone/nasal bridge), ears, forehead and cheeks. PPE-related itching, redness and dry skin mostly occurred. Several dressing applications were found to be effective in the prevention of PPE-related pressure ulcers and other skin problems that might develop especially on the facial region. Conclusion: PPE-related pressure ulcers and other skin problems were found to be higher among healthcare professionals. Data regarding the sealing of dressing applications against viral transmission in the prevention of PPE-related pressure ulcers and other skin problems are limited. It is estimated that future studies will be performed to prevent device-related pressure ulcers in healthcare workers. It is suggested that there is a need to conduct studies with larger samples where expert researchers make observations for pressure ulcers in order to determine the prevalence and incidence of PPE-related pressure ulcers.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Dermatoloji; Hemşirelik; Medicine; Health Sciences; Internal Medicine Sciences; Dermatology; Nursing; DERMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); HEMŞİRELİK; DERMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; COVID-19; Healthcare workers; Healthcare staff; Protective equipment; Pressure ulcer; SKIN INJURIES; PREVENTION; MASKS; Healthcare workers; Healthcare staff; Protective equipment; Pressure ulcer